Disparities in the Population Distribution of African American and Non-Hispanic White Smokers Along the Quitting Continuum. (December 2015) - Trinidad, Dennis R.; Xie, Bin; Fagan, Pebbles; Pulvers, Kim; Romero, Devan R.; Blanco, Lyzette; Sakuma, Kari-Lyn K.
Purpose . To examine disparities and changes over time in the population-level distribution of smokers along a cigarette quitting continuum among African American smokers compared with non-Hispanic Whites. Methods . Secondary data analyses of the 1999, 2002, 2005, and 2008 California Tobacco Surveys (CTS). The CTS are large, random-digit-dialed, population-based surveys designed to assess changes in tobacco use in California. The number of survey respondents ranged from n = 6, 744 to n = 12, 876 across CTS years. Current smoking behavior (daily or nondaily smoking), number of cigarettes smoked per day, intention to quit in the next 6 months, length of most recent quit attempt among current smokers, and total length of time quit among former smokers were assessed and used to recreate the quitting continuum model. Results . While current smoking rates were significantly higher among African Americans compared with non-Hispanic Whites across all years, cigarette consumption rates were lower among African Americans in all years. There were significant increases in the proportion of former smokers who had been quit for at least 12 months from 1999 (African Americans, 26.8% ± 5.5%; non-Hispanic Whites, 36.8% ± 1.6%) to 2008 (African Americans, 43.6% ± 4.1%; non-Hispanic Whites, 57.4% ± 2.9%). The proportion of African American former smokers in each CTS year was significantly lower than that of non-Hispanic Whites. Conclusions . Despite positive progression along the quitting continuum for both African American and non-Hispanic White smokers, the overall distribution was less favorable for African Americans. The lower smoking consumption levels among African Americans, combined with the lower rates of successful smoking cessation, suggest that cigarette addiction and the quitting process may be different for African American smokers.